PELAKSANAAN RELOKASI PEDAGANG JALAN M. HUSNI THAMRIN KE PASAR KELAKAP TUJUH DI KOTA DUMAI TAHUN 2017 – 2018 - Marmi Rosita Dewi; Rury Febrina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The implementation of the relocation of M. Husni Thamrin street traders to the Kelakap Tujuh market in Dumai City in 2017 - 2018 is a step or effort of the Dumai City government to alleviate the problem of M. Husni Thamrin street traders who established 2 traditional markets in an area that is not intended as a trading area. However, the implementation of the policy was not successful in alleviating the problem, this was marked by the return of traders to the M. Husni Thamrin street after relocation was less than 1 month relocated, while the implementation of the relocation had involved many government agencies in the City of Dumai. So the problem raised was regarding